Building Stronger Youth through Faith-Based Organizations: Integrating Organizational Management for Character Development - Alhafizh, Insan; Hayaturrohman, Hayaturrohman; Rahman, M Abdur; Rozinah, Siti (Al-Qalam Institue, 2025)
This study aims to examine the contribution of religious organization activities to the character development of adolescents in Indonesia. The method used was descriptive qualitative, with data collection techniques through direct observation and documentation of activities. The results indicate that routine activities such as youth religious study groups, Quranic recitation, basic leadership training, and social activities have shaped six key character values: religiosity, discipline, responsibility, independence, leadership, and social awareness. The development process was conducted in a participatory manner, with adolescents not only participating but also implementing and managing the activities. This research provides theoretical contributions to the field of community-based character education, particularly the role of mosques as effective non-formal educational institutions in internalizing moral and spiritual values in adolescents. However, a limitation of this study lies in the lack of use of interviews or group discussions that could explore the affective and reflective aspects of the participants. Future research is recommended to use more diverse methods and expand the scope of the research to gain a more comprehensive understanding.